Mengungkap peran kecerdasan buatan dalam memprediksi krisis ekonomi sebuah kajian algoritma dan aplikasi praktis - Jailani, Mohammad Shohibul Fajar (Maliki Interdisciplinary Journal, 2024)
Artificial intelligence (AI) is increasingly showing its potential in various fields, including in the prediction of economic crises. This study reviews the role of AI in detecting and predicting economic crises by utilizing various algorithms such as linear regression, ARIMA models, artificial neural networks, decision trees, and reinforcement learning. Through the analysis of complex and large data, AI is able to recognize patterns and trends that are difficult to detect by conventional methods. Practical applications of AI in economics include banking risk analysis, investment portfolio management, and the formulation of more responsive and adaptive economic policies. However, the use of AI also faces significant challenges, including data limitations, privacy issues, model complexity, and unpredictable global economic dynamics. By continuing to develop technologies and overcome these barriers, AI has the potential to become a highly effective tool in maintaining economic stability and managing risk proactively.